Hazard Management and Emergency Planning - Handmer, John (Routledge, 2013)
This book assesses critically the British approach to hazard management and emergency planning. It identifies the principal legal, organizational and cultural impediments to more effective hazard management and emergency planning, postulates explanations for the shortcomings in the British approach and examines a number of promising avenues for improving current practice. It comprises 18 chapters written by experts with a wide range of practical experience in the many different aspects of the field. Many of the authors introduce international perspectives and comparisons. From it all, the editors conclude, sadly: 'The overall hazard and emergency management approach currently adopted in Britain appears to be inadequate and current standards of protection appear to be inefficient for the 1990s and beyond'